2018
DOI: 10.1083/jcb.201710161
|View full text |Cite
|
Sign up to set email alerts
|

Desmoplakin maintains gap junctions by inhibiting Ras/MAPK and lysosomal degradation of connexin-43

Abstract: Desmoplakin (DP) is an obligate component of desmosomes, intercellular adhesive junctions that maintain the integrity of the epidermis and myocardium. Mutations in DP can cause cardiac and cutaneous disease, including arrhythmogenic cardiomyopathy (ACM), an inherited disorder that frequently results in deadly arrhythmias. Conduction defects in ACM are linked to the remodeling and functional interference with Cx43-based gap junctions that electrically and chemically couple cells. How DP loss impairs gap junctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 92 publications
2
42
0
Order By: Relevance
“…Thus, impaired cadherin binding by Trp excess or disturbed desmosomal function by reduced DSG2 or PG levels were interrupting proper electrical conduction with induction of arrhythmia. These data are in line with studies demonstrating that deficiency or mutation of desmosomal proteins can result in impaired GJ protein expression, localization and disrupted conduction of excitation . In addition, the function of the β 1 ‐adrenergic receptor inducing downstream signalling via cAMP was disturbed by impaired desmosomal composition or blocked cadherin binding.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Thus, impaired cadherin binding by Trp excess or disturbed desmosomal function by reduced DSG2 or PG levels were interrupting proper electrical conduction with induction of arrhythmia. These data are in line with studies demonstrating that deficiency or mutation of desmosomal proteins can result in impaired GJ protein expression, localization and disrupted conduction of excitation . In addition, the function of the β 1 ‐adrenergic receptor inducing downstream signalling via cAMP was disturbed by impaired desmosomal composition or blocked cadherin binding.…”
Section: Discussionsupporting
confidence: 89%
“…These data are in line with studies demonstrating that deficiency or mutation of desmosomal proteins can result in impaired GJ protein expression, localization and disrupted conduction of excitation. [27][28][29][30][31][32][33] In addition, the function of the β 1 -adrenergic receptor inducing downstream signalling via cAMP was disturbed by impaired desmosomal composition or blocked cadherin binding. This revealed, to our knowledge for the first time, the dependency of sufficient β 1adrenergic receptor function on proper desmosomal cohesion.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Green and colleagues demonstrated that Cx43 ubiquitination is involved in modulating gap junction levels in cardiac cells in response to loss of desmoplakin, a key component of desmosomes [138]. Desmosomes are cadherin-based intercellular adhesive junctions that have important roles in maintaining the integrity of the myocardium by tethering the intermediate filament cytoskeleton to sites of cell-cell adhesion [139].…”
Section: Role Of Connexin Ubiquitination In the Regulation Of Gap Junmentioning
confidence: 99%
“…Conditional knock-out of desmoplakin in mouse cardiac cells results in a significant reduction in Cx43 protein levels [140,141]. Mechanistically, loss of desmoplakin causes activation of the ERK1/2-MAPK pathway, which then stimulates phosphorylation of Ser279 and Ser282 within the C-terminal tail of Cx43 [138]. In neonatal rat ventricular cardiomyocytes, this phosphorylation event was found to be associated with increased Cx43 ubiquitination and degradation in lysosomes [138].…”
Section: Role Of Connexin Ubiquitination In the Regulation Of Gap Junmentioning
confidence: 99%
“…Curiously, some SAM syndrome patients present with chronic circumscribed, welldemarcated, hyperkeratotic, erythematous to brownish plaques mimicking EKV (Has et al, 2015;Cheng et al, 2016;Schlipf et al, 2016;Taiber et al, 2018). Desmosomal components such as desmoglein 2, desmoplakin (DP), plakoglobin, and plakophilin 2 can regulate Cx expression, trafficking, localization, and ubiquitination, especially in cardiac tissue (Oxford et al, 2007;Asimaki et al, 2009;Asimaki et al, 2014;Gehmlich et al, 2010;Patel et al, 2014;Kam et al, 2018). Therefore, we hypothesized that Dsg1 plays a role in GJ dynamics in the skin.…”
Section: Introductionmentioning
confidence: 99%